Social Ties and the Migration Decision of Temporal Migrant Workers - Gunawan Prayitno; Kakuya Matsushima; Kiyoshi Kobayashi (The Institute for Research and Community Services, Institut Teknologi Bandung, 2017)
Abstract. Social capital is a multi-faceted concept and is connected to all human interactions. We have simplified human interaction among three agents (young, adult, and old) and tried to develop an economic approach between social capital investment and migration decisions in rural areas in Indonesia. We divided the investment of social capital among human interactions of three agents living in three periods using overlapping generation theory. Social capital is made up of optimal individual investment decisions and accumulation processes. By utilizing a prototype of optimal individual investment decisions and the process of social accumulation, social capital is eventually produced. Social capital is the total stock of social capital of each agent in one period considering, the rate of discount and afterward using the relation to calculate the parameters to measure the social tie effect (strong and weak tie). The investment period in social capital has affected the parameters when the investment of time increases; in this situation, the social capital investment effect becomes smaller. The study shows that when social ties in a region are weak, all agents migrate to seek higher wages. Furthermore, all agents migrate abroad when social ties are weak. The model shows that the decision (to migrate or to stay) is influenced by social capital investment.Keywords. investment, migration, social capital, social tie.Abstrak. Modal sosial merupakan suatu konsep multifaset dan terkait dengan semua interaksi manusia. Kami telah menyederhanakan interaksi manusia di antara tiga agen (muda, dewasa, dan tua) dan mencoba mengembangkan pendekatan ekonomi antara investasi modal sosial dan keputusan migrasi di daerah pedesaan di Indonesia. Kami membagi investasi modal sosial di antara interaksi manusia dari tiga agen yang hidup dalam tiga periode dengan menggunakan teori generasi yang tumpang tindih. Modal sosial terdiri dari keputusan investasi dan akumulasi investasi yang optimal. Dengan memanfaatkan prototip keputusan investasi individu yang optimal dan proses akumulasi sosial, modal sosial akhirnya dihasilkan. Modal sosial adalah total stok modal sosial setiap agen dalam satu periode yang dihitung, tingkat diskon, dan kemudian digunakan relasi untuk menghitung parameter dalam mengukur efek ikatan sosial (ikatan kuat dan lemah). Periode investasi pada modal sosial telah mempengaruhi parameter ketika investasi waktu tengah meningkat; dalam situasi ini, efek investasi modal sosial menjadi lebih kecil. Studi tersebut menunjukkan bahwa ketika ikatan sosial di suatu wilayah lemah, semua agen bermigrasi untuk mencari upah yang lebih tinggi. Selanjutnya, semua agen bermigrasi ke luar negeri saat ikatan sosial lemah. Model tersebut menunjukkan bahwa keputusan (bermigrasi atau tinggal) dipengaruhi oleh investasi modal sosial.Kata Kunci. Investasi, migrasi, modal sosial, ikatan sosial.